1998
DOI: 10.1111/j.1365-2621.1998.tb15803.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage Temperature Effect on Histamine Formation in Big Eye Tuna and Skipjack

Abstract: Notable histamine formation (Ͼ30 mg/100g) was detected in big eye tuna (Thunnus obesus) and skipjack (Katsuwonus pelamis) captured in Azorean waters and stored for 1, 3 and 6 days at 22, 10 and 4ЊC, respectively. Higher levels (pϽ0.05) of histamine were produced by skipjack reflecting its higher histidine content. Measurements of pH or volatile basic nitrogen were not adequate for estimating the extent of histamine-related health hazard. Counts of histamine-forming bacteria increased during storage at 4 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 24 publications
7
28
0
8
Order By: Relevance
“…Prolong exposure to room temperature during defrost might increase histamine concentration in tuna. Silva et al (1998) reported rise of histamine content at 10 and 4 C, but notable amounts were detected after 3 days at 10 C and 6 days at 4 C. A study conducted by Rossano et al, (2006), are in agreement that histamine level increase with time of storage when stored at 4 C.…”
Section: Resultssupporting
confidence: 72%
“…Prolong exposure to room temperature during defrost might increase histamine concentration in tuna. Silva et al (1998) reported rise of histamine content at 10 and 4 C, but notable amounts were detected after 3 days at 10 C and 6 days at 4 C. A study conducted by Rossano et al, (2006), are in agreement that histamine level increase with time of storage when stored at 4 C.…”
Section: Resultssupporting
confidence: 72%
“…Unlike histamine decomposition at 0°C, no decomposition took place at 20°C which implies that such a high temperature might inhibit the growth of histamine decomposing bacteria (Sato et al, 1994). Rapid histamine accumulation was found also in skip jack which maintained its safety for only one day at 22°C (Silva et al, 1998).…”
Section: Histamine Formationmentioning
confidence: 98%
“…Many scientists have studied the effects of storage temperatures on histamine formation in fish, and their results have been very often ambiguous (Guillén-Velasco, Ponce-Alquicira, Farrés-González Saravia, & GerreroLegarreta, 2004;Silva, Ponte, & Dapkevicius, 1998). This can be explained by the differences in the composition and the level of bacterial flora in the fish.…”
Section: Introductionmentioning
confidence: 96%
“…Histamine remained consistently higher than the other four biogenic amines at 11 ο C in all four fish lots irrespective of treatment, probably due mainly to the effect of temperature, but also possibly due to the higher bacterial load introduced by skin contamination in the case of the contaminated fish. Silva et al (1998) observed increasingly higher amounts of histamine, i.e., greater than 550 ppm in big eye tuna after three days at 10 ο C. Our experiments at 11 ο C showed that greater than 500 ppm of histamine were formed after about three days of storage. Putrescine and cada- verine are formed from the decarboxylation of ornithine and lysine, respectively .…”
Section: Journal Of Aquatic Food Product Technologymentioning
confidence: 70%